MULTIPURPOSE HYDRO-DRIVE OF MOBILE MACHINES - A. V. Korolkevich; M. I. Zhylevich; V. S. Shevchenko; V. S. Korolkevich (Наука и техника)
The paper analyzes problems concerning modernization of  hydro-drives and higher efficiency of their operation. A principal  scheme of a self-propelled machine hydro-drive ensuring non-stage regulation, reverse and braking of the machine and operational equipment is proposed in paper. The scheme significantly expands operational capabilities of the hydro-drive and improves its power and economic indices.